2005
DOI: 10.1111/j.1365-2117.2005.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Burial and exhumation history of Pennsylvanian strata, central Appalachian basin: an integrated study

Abstract: An inferred burial and exhumation history of Pennsylvanian strata in the central Appalachian foreland basin is constrained by integrating palaeothermometers, geochronometers and estimated palaeogeothermal gradients. Vitrinite reflectance data and fluid inclusion homogenization temperatures indicate that burial of Lower and Upper Pennsylvanian strata of the Appalachian Plateau in West Virginia exceeded ∼4.4 km during the late Permian and occurred at a rate of ∼100 m Myr−1. Exhumation rates of ∼10 m Myr−1 from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 62 publications
4
31
0
Order By: Relevance
“…In a study of variations in joint intersection style observed in Middle and Upper Devonian shales within the Appalachian Basin, Lash and Engelder (2009) concluded that the propagation of east-northeast-striking joints happened during two distinct phases during the evolution of the basin, as opposed to solely in response to fluid overpressures during maximum burial that occurred during the Late Permian (Blackmer et al, 1994;Reed et al, 2005). Initial fluid-driven east-northeaststriking joints formed during the early stages of the Alleghanian orogeny (Lash and Engelder, 2009), which were then reactivated under the coaxial contemporary stress regime (S Hmax , ∼072°± 6°; Plumb and Cox, 1987) through a combination of thermal contraction, Poisson's contraction, and/or lateral strain caused by rapid exhumation during the late Miocene (Lash and Engelder, 2009).…”
Section: Evidence For Secondary Porosity Development Related To Exhummentioning
confidence: 98%
See 2 more Smart Citations
“…In a study of variations in joint intersection style observed in Middle and Upper Devonian shales within the Appalachian Basin, Lash and Engelder (2009) concluded that the propagation of east-northeast-striking joints happened during two distinct phases during the evolution of the basin, as opposed to solely in response to fluid overpressures during maximum burial that occurred during the Late Permian (Blackmer et al, 1994;Reed et al, 2005). Initial fluid-driven east-northeaststriking joints formed during the early stages of the Alleghanian orogeny (Lash and Engelder, 2009), which were then reactivated under the coaxial contemporary stress regime (S Hmax , ∼072°± 6°; Plumb and Cox, 1987) through a combination of thermal contraction, Poisson's contraction, and/or lateral strain caused by rapid exhumation during the late Miocene (Lash and Engelder, 2009).…”
Section: Evidence For Secondary Porosity Development Related To Exhummentioning
confidence: 98%
“…The Upper Cretaceous Mesaverde Group in the southern Piceance Basin was exhumed by approximately 1800 m (∼5905 ft) during the Neogene (Nuccio and Roberts, 2003;Fall et al, 2012), whereas Pennsylvanian strata in the central Appalachian Basin have been exhumed by approximately 4400 m (∼14,435 ft) since the Late Permian (Blackmer et al, 1994;Reed et al, 2005). Although the timing of exhumation from maximum burial depths in the Fort Worth Basin is a matter of some debate (e.g., mid-Cretaceous; Montgomery et al, 2005;Late Triassic;Ewing, 2006), it is agreed that the Mississippian Barnett Shale has experienced more than 1500 m (∼4920 ft) of net exhumation (Jarvie et al, 2005Montgomery et al, 2005;Ewing, 2006).…”
Section: Comparisons With Tight and Shale Oil And/or Gas Plays In Thementioning
confidence: 98%
See 1 more Smart Citation
“…Utilizing a combination of maximum paleotemperatures indicators, subsidence and thermal modeling, and geologic constraints, deposition of the sedimentary overburden and maximum temperatures likely occurred sometime between the Alleghenian Orogeny in the late Paleozoic and the Early Jurassic (e.g. Johnsson, ; Levine, ; Beaumont, Quinlan, & Hamilton, ; Reed et al, ; Lash & Blood, ).…”
Section: Geologic Settingmentioning
confidence: 99%
“…temperature and timing), cooling rates, exhumation histories, and hydrocarbon source rock maturation levels within sedimentary basins (e.g. Green, Duddy, Gleadow, & Lovering, ; Naeser, Naeser, & McCulloh, ; Gallagher, Brown, & Johnson, ; Reed, Spotila, Eriksson, & Bodnar, ; Green & Duddy, ; Ketcham, ; Malusà & Fitzgerald, ). AFT thermochronology applied to sedimentary basin strata has the potential to determine maximum paleotemperatures up to ~100–120°C, as well as constrain the timing and rates of cooling (e.g.…”
Section: Introductionmentioning
confidence: 99%